Decision Support System in E-Commerce in Purchasing Saw with Method Woven Fabric - ANUARIDLO, Mochamad Aldi Yusuf; FIRLIANA, Rina; DANIATI, Erna (Journal of Entrepreneurial and Business Diversity, 2024)
Purpose: Choosing ikat woven fabric has several predetermined criteria. These criteria include price, quality, product type, and color. The decision support system for selecting ikat fabric purchases for buyers in e-commerce using the SAW (simple additive weighting) method is a system that can determine the results of the decision to select one of the ikat fabrics based on predetermined criteria and alternatives.Methodology:The SAW method is one of the decision-making methods often used in DSS. The research method refers to a literature study that aims to find references that suit the problem, then observation by collecting data at the specified research location and interviewing the owner and one of the MSME employees to obtain detailed information.Findings: This research determines the purchase of good woven fabric via e-commerce for ikat woven fabric products in Bandar Kidul village, Mojoroto subdistrict, Kediri city. Calculating the best-woven fabric for ikat products can use the simple additive weight (SAW) method so that one best-selling ikat fabric, namely silk woven fabric, is selected and meets the requirements, with a score of 0.76675.Implication:Based on this research, we can determine which suitable woven fabrics to buy using e-commerce for ikat woven fabric products in Bandar Kidul village, Mojoroto subdistrict, Kediri city. The simple additive weight (SAW) method can calculate the best-woven fabric for ikat products.